Bible references in the “Universal History” by Stepanos Taronetsi Asoghik - Vardanyan, Lusine (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Յայտնի է, որ միջնադարեան պատմագիրներն իրենց երկերը կառուցում էին ըստ Սուրբ Գրքի աշխարհայեցողութեան, դէպքերը մեկնաբանում մարգարէական կանխասացութիւններով եւ որպէս փաստարկ յաճախ ուղղակի կամ անուղղակի վկայակոչում էին Աստուածաշնչեան տեղիները ։ Այս առումով բացառութիւն չէ նաեւ Ստեփանոս Տարօնեցի Ասողիկի Պատմութիւնը (Ժ.—ԺԱ. դդ.), որի ընդհանրական լինելն արդէն իսկ Սուրբ Գրքի ձեւաբովանդակային նմանութիւնից է բխում։ Յօդուածում դիտարկւում են երկում առկայ ուղղակի մէջբերումները եւ դրանց նշանակութիւնն Ասողիկի բնագրի համար։ Известно, что средневековые авторы в частности историки выстраивали свои труды в соответствии мировоззрения Священной Книги, толковали события пророческими предсказаниями и часто прямо или косвенно ссылались на библейские отрывки в качестве аргумента. В этом отношении не является исключением и «История Степаноса Таронеци Асогика». В статье исследуются прямые цитаты из священного Писания и их значение для труда Степаноса Асогика. Medieval historians are known to have constructed their writings according to the biblical worldview, interpreting events with prophetic predictions, often directly or indirectly citing biblical passages as arguments. The “History” of Stepanos Taronetsi Asoghik (10th-11th centuries) is no exception in this respect, the universality of which already originates from similarities between the form and content of the Holy Bible. The article discusses direct quotations presented in the work and their significance for Asoghik’s text. It is interesting to compare these quotations with the relevant verses of the Bible, which reveals the close connection between the two texts, more precisely, the derivation of the historical work of the 10th-11th centuries from the Scriptures.
Keywords: Historical-Philological Studies